Effects of bolt sizes and interlocking key joint precast slab shear connectors on the performance of steel-concrete composite beam - Loqman, Nadiah (2020)
Conventional composite steel-concrete beams have been recognized to exhibit stronger structural characteristics, in terms of strength and stiffness, when compared to pure steel or reinforced concrete beams. However, currently, most of the steel beam is fully attached to the concrete slab; this means that the shear connectors are welded through the steel decking on to the steel beam and cast into the concrete slab to fulfil the necessary shear connection. In order to achieve a sustainable structural system, bolted shear connectors are used to connect the precast concrete slabs and steel beam in the composite beam. An interlocking tongue and groove joints between the precast concrete slabs are also introduced into the composite system. Thus, the main objective of this study is to measure the structural behaviour of a composite beam using an interlocking precast concrete slab and bolted shear connector under flexural static load. The structural behaviour of the composite beam that is examined is the stiffness, strength, ductility, end slip between steel-concrete interface and failure mode. For this purpose, an experimental test was conducted on six number of full-scale composite beams. The variables are the effect of an interlocking joint and the size of bolt. This work also incorporates Finite Element (FE) modelling to provide a comparison with the existing experimental test result. The test results demonstrated that the composite beams having a precast concrete slab with interlocking tongue and groove joint have better initial stiffness, ultimate load and deflection by 12.3%, 1.9% and 10.6%, respectively when compared to the precast concrete slab without the interlocking joint which proved that the interlocking joint is an effective mechanism to transfer the applied load and improve the strength and stiffness of the composite beam. The behaviour of composite beams with higher size of bolt also showed a higher ultimate load and deflection by 10.8% and 18.8%, respectively than the composite beam with a lower size of bolt under flexural load. This demonstrated that a bigger diameter of the bolt has a higher load capacity and ductility that can hold both of the concrete slab and steel beam together more effectively. The end slip of the composite beams with bolted shear connectors does not show any significant slip between the steelconcrete interface with only 2 mm of slip which is the summation of the bolt clearance hole. The comparison made from FE modelling showed a good agreement at the postelastic range (non-linear part) between the experimental test result and the Finite Element (FE) result.